2017
DOI: 10.1038/s41598-017-09868-w
|View full text |Cite
|
Sign up to set email alerts
|

fNIRS can robustly measure brain activity during memory encoding and retrieval in healthy subjects

Abstract: Early intervention in Alzheimer’s Disease (AD) requires novel biomarkers that can capture changes in brain activity at an early stage. Current AD biomarkers are expensive and/or invasive and therefore unsuitable for use as screening tools, but a non-invasive, inexpensive, easily accessible screening method could be useful in both clinical and research settings. Prior studies suggest that especially paired-associate learning tasks may be useful in detecting the earliest memory impairment in AD. Here, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 90 publications
4
26
0
1
Order By: Relevance
“…Using the fOLD toolbox, a list of the selected fNIRS channels and corresponding Brodmann’s areas were then created for ease of comparison with fMRI literature ( Table 1 ). The probe contained 16 sources, 15 long separation detectors (approximately 3 cm distance from the source), and 8 short separation detectors (approximately 8 mm distance from each source; Brigadoi and Cooper, 2015 ; Yücel et al, 2015 ; Jahani et al, 2017 ; Nemani et al, 2018 ). This configuration resulted in a total of 54 channels in which 46 are long and 8 are short separation source-detector pairs ( Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%
“…Using the fOLD toolbox, a list of the selected fNIRS channels and corresponding Brodmann’s areas were then created for ease of comparison with fMRI literature ( Table 1 ). The probe contained 16 sources, 15 long separation detectors (approximately 3 cm distance from the source), and 8 short separation detectors (approximately 8 mm distance from each source; Brigadoi and Cooper, 2015 ; Yücel et al, 2015 ; Jahani et al, 2017 ; Nemani et al, 2018 ). This configuration resulted in a total of 54 channels in which 46 are long and 8 are short separation source-detector pairs ( Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, the research studies compared the hemodynamic response of a patient with that of healthy control (HC) and determined neuroanatomical or neurofunctional differences at the group level. Most AD/MCI detection studies typically employed the HbO/ HbR (Jahani et al, 2017;Perpetuini et al, 2017;Vermeij et al, 2017;Katzorke et al, 2018;Yoon et al, 2019) and relative temporal features such as the mean value, slope value, number of active channels, peak location, skewness, and kurtosis (Yap et al, 2017;Li et al, 2018a), and they determined the significant differences for comparison. The straightforwardness and interpretability of this methodology has led to considerable advances in our comprehension of the neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…5(a) (top) shows the designed probe used for the study and the points corresponding to the prefrontal cortex. 101 The results revealed that novel face encoding required activation of le inferior frontal cortex and inactivation of medial-to-superior frontal cortices which is shown to be signicant from the color bar as shown in Fig. 5(a) (bottom le).…”
Section: Pre-clinical Imaging Technologiesmentioning
confidence: 83%